Induced Sputum for the Diagnosis of Pulmonary Tuberculosis: Is It Useful in Clinical Practice?. Issue 4 (2010) - Olsen, S-R; Long, R; Tyrrell, GJ; Kunimoto, D
Abstract : BACKGROUND: Diagnosing pulmonary tuberculosis (PTB) is challenging in patients who are unable to spontaneously expectorate. Published evidence suggests that induced sputum (IS) is the least invasive and most cost-effective method of diagnosis, and should be used before fibre-optic bronchoscopy (FOB). METHODS: The medical records of 337 adults treated for PTB in northern Alberta between 1997 and 2007 were reviewed to determine whether local practice patterns reflect the evidence. Microbiological data were collected from the Provincial Laboratory for Public Health. Demographic information was collected from the patients' charts. RESULTS: A total of 8.5% (26 of 307) of PTB patients had IS collected, whereas 35.8% (110 of 307) underwent FOB. Among FOB patients, 56.4% (62 of 110) had no sputum sent before the procedure and 29% (18 of 62) of these patients were smear positive. Only five patients referred for FOB had IS sent previously. There were no demographic factors predictive of IS use, whereas being an inpatient at a teaching facility or having a nodule or mass on chest x-ray was predictive of FOB referral. Because so few IS samples were available, not all patients had spontaneously expectorated sputum, IS and FOB tests performed; thus, the calculated yields were not comparable with one another. CONCLUSIONS: Despite published evidence recommending IS collection before FOB referral in suspected PTB patients, clinicians in our health region appeared to prefer early FOB over IS by a large margin. This practice pattern is less cost effective and exposes patients and health care workers to greater risk. Further research is needed to identify the reasons for the underuse of sputum induction.